Proceedings of the Seventh Annual ACM/IEEE International Conference on Human-Robot Interaction 2012
DOI: 10.1145/2157689.2157805
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of robots in home organization

Abstract: Technologists have long wanted to put robots in the home, making robots truly personal and present in every aspect of our lives. It has not been clear, however, exactly what these robots should do in the home. The difficulty of tasking robots with home chores comes not only from the significant technical challenges, but also from the strong emotions and expectations people have about their home lives. In this paper, we explore one possible set of tasks a robot could perform, home organization and storage tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Within the field of HRI, convincing research is typically strongly supported by user studies to help prove the effectiveness of new techniques (Lee et al, 2012;Cakmak & Thomaz, 2012;Kahn et al, 2012;Pantofaru, Takayama, Foote, & Soto, 2012;Morales Saiki et al, 2012). Integration of user studies into the design, development and evaluation of new techniques has been shown to result in more useable methods (Suay, Toris, & Chernova, 2012), whereas development of algorithms in isolation risks biasing usability towards expert users.…”
Section: Introductionmentioning
confidence: 99%
“…Within the field of HRI, convincing research is typically strongly supported by user studies to help prove the effectiveness of new techniques (Lee et al, 2012;Cakmak & Thomaz, 2012;Kahn et al, 2012;Pantofaru, Takayama, Foote, & Soto, 2012;Morales Saiki et al, 2012). Integration of user studies into the design, development and evaluation of new techniques has been shown to result in more useable methods (Suay, Toris, & Chernova, 2012), whereas development of algorithms in isolation risks biasing usability towards expert users.…”
Section: Introductionmentioning
confidence: 99%
“…This situation confirms what Takayama et al [19] found: "people would feel more positively toward robots doing occupations with people rather than in place of people". Transposing this approach to homes for a use with children, we developed a robot to help tidying-up the children's room, which has been considered as an interesting task by previous studies [3,4].…”
Section: State Of the Artmentioning
confidence: 99%
“…Only 13% of the European citizen think robots should be applied in priority to "domestic use, such as cleaning". Also among researchers it has not been clear what a robot exactly should do in homes [3]. Pantofaru et al [3] explored the role of robots in home organization (tidying, storing), and found that robots could have a potentially high impact on this.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To copy otherwise, to republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee. enumerating tasks include ICF (International Classification of Functioning) [2], ADL (Activities of Daily Living) [5], interviews with people in their homes [4] and surveys [6].…”
Section: Introductionmentioning
confidence: 99%